Anergic T-lymphocyte clones have altered inositol phosphate, calcium, and tyrosine kinase signaling pathways. - Gajewski, T F (1994)
Full activation of TH1 helper T lymphocytes requires ligation of the specific T-cell antigen receptor (TCR) and a second signal provided by costimulator molecule(s) expressed on particular antigen-presenting cells. Stimulation via the TCR complex alone generates a subsequent unresponsive state characterized by an inability to produce interleukin 2. We report here that such anergic cells exhibit multiple alterations in TCR-associated signaling. The basal levels of intracellular free calcium and phosphatidylinositol 1,4,5-trisphosphate are elevated in anergic cells, and the levels fail to increase significantly upon subsequent restimulation. Examination of phospholipase C-gamma 1 reveals evidence for post-translational modification, correlating with increased tyrosine phosphorylation of the molecule. Tyrosine phosphorylation of additional substrates identified from whole-cell lysates also is altered compared to untreated cells, suggesting a modification in net tyrosine kinase activity. Although the level of kinase activity present in TCR/CD3 or Lck immunoprecipitates is modestly altered after induction of anergy, there is a dramatic increase in specific Fyn-associated tyrosine kinase activity in anergic cells and increased phosphorylation of a 110-kDa protein that is coimmunoprecipitated with Fyn. These results are consistent with a model in which anergic TH1 lymphocytes display a fundamental alteration in TCR-mediated tyrosine kinase activity, associated with changes in phospholipase C-gamma 1, inositol phosphates, and intracellular free calcium.